2023
DOI: 10.3390/pharmaceutics15061653
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy as a Promising Way to Fight Oral Cancer

Abstract: Oral cancer is a highly aggressive tumor with invasive properties that can lead to metastasis and high mortality rates. Conventional treatment strategies, such as surgery, chemotherapy, and radiation therapy, alone or in combination, are associated with significant side effects. Currently, combination therapy has become the standard practice for the treatment of locally advanced oral cancer, emerging as an effective approach in improving outcomes. In this review, we present an in-depth analysis of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 335 publications
0
3
0
Order By: Relevance
“…Besides, the chemotherapy drugs are mostly cytotoxic drugs, which will cause more serious side effects (Deepak et al., 2023 ; Peña-Corona et al., 2023 ). Therefore, combined administration has attracted more and more attention in anti-tumor research, which can not only reduce the occurrence of drug resistance, improve therapeutic efficacy, but also reduce the incidence of side effects by acting on multiple targets (Li et al., 2023 ; Nguyen et al., 2023 ; Silva et al., 2023 ). Our research group has attempted to combine liver-protective drugs (such as glycyrrhizin, glycyrrhetinic acid, oleanolic acid, diammonium glycyrrhizinate, silymarin, and puerarin) to counteract the toxic effect of ACGs, but no combination has been found that can reduce the toxicity while maintaining the efficacy, and the combination almost invariably significantly reduced the anti-tumor effect of ACGs in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the chemotherapy drugs are mostly cytotoxic drugs, which will cause more serious side effects (Deepak et al., 2023 ; Peña-Corona et al., 2023 ). Therefore, combined administration has attracted more and more attention in anti-tumor research, which can not only reduce the occurrence of drug resistance, improve therapeutic efficacy, but also reduce the incidence of side effects by acting on multiple targets (Li et al., 2023 ; Nguyen et al., 2023 ; Silva et al., 2023 ). Our research group has attempted to combine liver-protective drugs (such as glycyrrhizin, glycyrrhetinic acid, oleanolic acid, diammonium glycyrrhizinate, silymarin, and puerarin) to counteract the toxic effect of ACGs, but no combination has been found that can reduce the toxicity while maintaining the efficacy, and the combination almost invariably significantly reduced the anti-tumor effect of ACGs in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy is recommended over mono-drug therapy as a means of reducing treatment time, preventing medication resistance, and improving treatment performance [1]. Although combination therapy was originally suggested in 1950, it has picked up popularity in recent years due to notable advancements regarding the management of conditions such as cancer, diabetes, neurological, metabolic, asthma, cardiovascular, HIV, malaria, and others [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Hormone therapy, primarily tailored to hormone receptor-positive cases, contributes to tumor regression and stability, potentially extending survival by several months [13]. Combination therapies can synergistically enhance treatment efficacy and survival rates by incorporating a personalized approach that takes into account individual patient and tumor characteristics [14]. However, metastatic tumors often demonstrate a remarkable capacity to adapt and evolve, resulting in resistance to various treatment modalities.…”
Section: Introductionmentioning
confidence: 99%